Prophylactic platelet transfusions in patients with blood malignancies: cost analysis of a randomized trial. Issue 10 (15th May 2014) - Campbell, Helen E.; Estcourt, Lise J.; Stokes, Elizabeth A.; Llewelyn, Charlotte A.; Murphy, Michael F.; Wood, Erica M.; Stanworth, Simon J.; TOPPS Study Investigators
<x xml:space="preserve">Abstract</x> Background This cost analysis uses data from a randomized trial comparing a no prophylaxis versus prophylactic platelet (PLT) transfusion policy (counts <10 × 109/L) in adult patients with hematologic malignancies. Results are presented for all patients and separately for autologous hematopoietic stem cell transplantation (HSCT) (autoHSCT) and chemotherapy/allogeneic HSCT (chemo/alloHSCT) patients. Study Design and Methods Data were collected to 30 days on PLT and red blood cell (RBC) transfusions, major bleeds, serious adverse events, critical care, and hematology ward stay. Data were costed using 2011 to 2012 UK unit costs and converted into US$. Sensitivity analyses were performed on uncertain cost variables. Results Across the whole trial no prophylaxis saved costs compared to prophylaxis: −$1760 per patient (95% confidence interval [CI], −$3250 to −$249; p < 0.05). For autoHSCT patients there was no cost difference between arms: −$110 per patient (95% CI, −$1648 to $1565; p = 0.89). For chemo/alloHSCT patients no prophylaxis cost significantly less than prophylaxis: −$5686 per patient (95% CI, −$8580 to −$2853; p < 0.01). The cost impact of no prophylaxis differed significantly between subgroups. Sensitivity analyses varying daily treatment costs and ward stay for chemo/alloHSCT patients reduced cost differences to −$941 per patient (p = 0.21) across the whole trial and −$2927 per patient (p < 0.05) in chemo/alloHSCT subgroup. Conclusions It is unclear whether a no‐prophylaxis policy saves costs overall. In chemo/alloHSCT patients cost savings are apparent but their magnitude is sensitive to a number of variables and must be considered alongside clinical data showing increased bleeding rates. In autoHSCT patients savings generated through lower PLT use in no‐prophylaxis arm were offset by cost increases elsewhere, for example, additional RBC transfusions. Cost‐effectiveness analyses of alternative PLT transfusion policies simultaneously considering costs and patient‐reported outcomes are warranted.